PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN ASING DAN JENIS INDUSTRI TERHADAP KINERJA KEUANGAN YANG DIMEDIASI OLEH KINERJA LINGKUNGAN (STUDI EMPIRIS PADA PERUSAHAAN PESERTA PROPER YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016) - Tiurmauli, Kristine; Rokhmawat, Andewi; Fathoni, Ahmad Fauzan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study was aims to examine the effect of firm size, foreign ownership and industry type on financial performance with environmental performance as a mediation variable. Environmental performance is measured by using the PROPER rating published by the Ministry of Environment of the Republic of Indonesia and the company's financial performance is measured by using ROA. The research method used in this research was quantitative method that aimed to examine environmental performance in mediating the effect of Company Size, Foreign Ownership and Industry Type on Financial Performance. This research used 37 companies as the sample. The sampling technique was chosen based on purposive sampling that the must be companies listed in Indonesia Stock Exchange and were rated PROPER during period 2014-2016. To analysis the data, this research used path analyze by using Statistical Package for the Social Sciences (SPSS). The result of this research showed that firm size has a positive effect on environmental performance but has no effect on financial performance. Foreign ownership has a positive effect on environmental performance and financial performance, and industry type has no effect neither on environmental performance nor financial performance. Furthermore, the environmental performance in this study is able to mediate the effect of firm size to financial performance but not to foreign ownership and industry type. In line with previous research, environmental performance has a positive effect on company performance. By performing better environmental performance, the company can improve profitability, build its image and reputation, and increase public trust and other stakeholders on the legitimacy of the company.Keywords : Environmental Performance, PROPER, Firm Size, Foreign Ownership, Industry Type and Financial Performance.